Marriage Market Signals and Homeownership for the Never Married - Kusum Mundra; Ruth Uwaifo Oyelere (Institute of Labor Economics (IZA), 2018)
There is a growing trend of buying homes among the single population in the U.S. This trend has been referred to as "Going Solo" and is particularly evident among women who are the focus of our study. In this paper we investigate the hypothesis that homeownership probabilities can be affected by marriage market expectations and pessimistic marriage market expectations may raise home buying probabilities among never married singles. We focus solely on the sub population called the never married single females and our results provide evidence consistent with the above hypothesis. In particular, we find that up to a certain threshold, the probability of homeownership decreases when the marriage market prospect indicator improves and there is evidence of heterogeneity in this relationship across race, education level, age group and motherhood status.
Keywords: J1; J12; R21; 330; home ownership; never married singles; marriage market; sex ratios; marriage rates; single females